PEMANFAATAN MEDIA PEMBELAJARAN AUDIO VISUAL TERHADAP MINAT BELAJAR PESERTA DIDIK KELAS V DI SD IT IRSYADUL IBAD 2 PANDEGLANG - Adya Pribadi, Reksa; Rahmawati, Ipat (STKIP Subang, 2021)
Based on the research, it was found that the lack of development of learning media resulted in boring learning and students who experienced a lack of interest in learning activities which resulted in a lack of material delivered and obtained by students. The objectives to be achieved through this research are to determine the use of audio-visual learning media on the learning interest of fifth grade students at Sdit Irsyadul Ibad 2 Pandeglang. The method taken by the researcher through descriptive qualitative research method which in this method to examine a phenomenon the data used through interviews, observations and questionnaires. The results of this study were students actively participated in learning activities through asking questions, the class became effective because students were very focused on audio-visual learning media and the material provided was well conveyed to students so as to create maximum learning outcomes.